Cascade Immune Activation of Self‐Delivery Biomedicine for Photodynamic Immunotherapy Against Metastatic Tumor. Issue 3 (11th November 2022) - Zheng, Rong‐Rong; Zhao, Lin‐Ping; Yang, Ni; Chen, Zu‐Xiao; Kong, Ren‐Jiang; Huang, Chu‐Yu; Rao, Xiao‐Na; Chen, Xin; Cheng, Hong; Li, Shi‐Ying
Abstract: Photodynamic therapy (PDT) can generate reactive oxygen species (ROS) to cause cell apoptosis and induce immunogenic cell death (ICD) to activate immune response, becoming a promising antitumor modality. However, the overexpressions of indoleamine 2, 3‐dioxygenase (IDO) and programmed cell death ligand 1 (PD‐L1) on tumor cells would reduce cytotoxic T cells infiltration and inhibit the immune activation. In this paper, a simple but effective nanosystem is developed to solve these issues for enhanced photodynamic immunotherapy. Specifically, it has been constructed a self‐delivery biomedicine (CeNB) based on photosensitizer chlorine e6 (Ce6), IDO inhibitor (NLG919), and PD1/PDL1 blocker (BMS‐1) without the need for extra excipients. Of note, CeNB possesses fairly high drug content (nearly 100%), favorable stability, and uniform morphology. More importantly, CeNB‐mediated IDO inhibition and PD1/PDL1 blockade greatly improve the immunosuppressive tumor microenvironments to promote immune activation. The PDT of CeNB not only inhibits tumor proliferation but also induces ICD response to activate immunological cascade. Ultimately, self‐delivery CeNB tremendously suppresses the tumor growth and metastasis while leads to a minimized side effect. Such simple and effective antitumor strategy overcomes the therapeutic resistance against PDT‐initiated immunotherapy, suggesting a potential for metastatic tumor treatment in clinic. Abstract : Self‐delivery biomedicine (CeNB) is developed based on the assembly of photosensitizer chlorine e6 (Ce6), IDO inhibitor (NLG919), and PD1/PDL1 blocker (BMS‐1). CeNB‐mediated IDO inhibition and PD1/PDL1 blockade greatly improve the immunosuppressive tumor microenvironments (ITM) to promote immune activation and cutoff the immune evasion of tumor cells. The photodynamic immunotherapy of CeNB tremendously inhibits the tumor growth and metastasis by cascade immune activation.